React-bratus: Visualising React Component Hierarchies - Boersma, Stephan; Lungu, Mircea (2021 Working Conference on Software Visualization (VISSOFT), 2021)
We report on the development of react-bratus, a prototype providing developers with an interactive web-based component hierarchy visualization for React-based projects. We continuously evaluate react-bratus in multiple iterations with junior developers and find that component hierarchy visualizations are a promising tool for helping novice developers reverse engineer React-based applications.